Advanced image processing techniques and applications - Kumar, N. Suresh, 1979-; Sangaiah, Arun Kumar, 1981-; Arun, M., 1979-; Anand, S. (Engineer) (Advances in computational intelligence and robotics (ACIR) book series, 2017)
"This book is an essential reference publication for the latest research on digital image processing advancements. Featuring expansive coverage on a broad range of topics and perspectives, such as image and video steganography, pattern recognition, and artificial vision"--